Basic principles and constitutional legal framework of freedom of information - Abdul Jalil, Juriah (IIUM Press, 2011)
Vision 2020 envisages that Malaysia becomes a fully developed democratic nation in terms ofnational unity and social-cohesion, economy, social justice, political stability, system ofgovernment, quality oflifu, social and spiritual values, national pride and confidence. To achieve this vision, freedom ofinformation becomes a central factor for the government and the public in building a democratic nation in accordance with the spirit ofVision 2020. In this aspect, information becomes the oxygen of democracy whereby the people need information to participate in the affairs ofsociety and in decision making process while the government need information and feedback from the society to ensure good governance